Can in-work benefits improve social inclusion in the Southern European countries? - Francesco Figari (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper analyses the effects of implementing a family-based and an individually-based in-work benefit in the Southern European Countries using EUROMOD, the EU-wide tax-benefit microsimulation model. In-Work Benefits (IWBs) are means-tested cash transfers given to individuals, through the tax system, conditional on their employment status. They are intended to enhance the incentives to accept work and redistribute resources to low income groups. The research confirms the presence of a trade off between the redistributive and the incentive effects of the different policies. Family-based in-work benefits are better targeted on the poorest households, in particular in Italy and Portugal. Individually-based policies lead to greater incentives to work, in particular in Italy and in Greece. Individually-based IWBs seem to be more efficient if the enhancement of the labour market participation of women in couples is of fundamental concern.
Keywords: H53; I32; I38; 330; work benefits; fiscal microsimulation; poverty; female labour market participation; Steuerbegünstigung; Weibliche Arbeitskräfte; Niedrigeinkommen; Mikrosimulation; EU-Staaten; Südeuropa